CHATGPT AND OTHER AI ASSISTANTS IN ENGLISH WRITING CLASSES: A BLESSING OR A CURSE? - Zokirova Marjona Xislatjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This paper explores the role of ChatGPT and other AI assistants in English writing classes, evaluating whether they serve as beneficial tools or pose challenges for both students and educators. It discusses the potential advantages of AI in providing personalized feedback, enhancing writing fluency, and supporting language learning. Conversely, the paper addresses concerns regarding academic integrity, over-reliance on technology, and the impact on students' critical thinking skills. Through analysis of current literature and classroom observations, the study provides insights into integrating AI responsibly in English writing instruction.